Prediction of in vivo bone forming potency of bone marrow-derived human mesenchymal stem cells - Janicki, Patricia; Boeuf, Stephane; Steck, Eric; Egermann, Marcus; Kasten, Philip; Richter, Wiltrud (European cells & materials, 2011)
Human mesenchymal stem cells (MSC) have attracted much attention for tissue regeneration including repair of non-healing bone defects. Heterogeneity of MSC cultures and considerable donor variability however, still preclude standardised production of MSC and point on functional deficits for some human MSC populations. We aimed to identify functional correlates of donor-dependency of bone formation in order to develop a potency assay predicting the therapeutic capacity of human MSC before clinical transplantation. MSC from 29 donors were characterised in vitro and results were correlated to bone formation potency in a beta-tricalcium-phosphate (β-TCP)-scaffold after subcutaneous implantation into immunocompromised mice. In contrast to osteogenic in vitro differentiation parameters, a doubling time below 43.23 hours allowed to predict ectopic bone formation at high sensitivity (81.8%) and specificity (100%). Enriched conditions adapted from embryonic stem cell expansion rescued bone formation of inferior MSC populations while growth arrest of potent MSC by mitomycin C abolished bone formation, establishing a causal relationship between neo-bone formation and growth. Gene expression profiling confirmed a key role for proliferation status for the bone forming ability suggesting that a rate limiting anabolism and open chromatin determined and predicted the therapeutic potency of culture-expanded MSC. Proliferation-based potency testing and switch to enriched expansion conditions may pave the way for standardised production of MSC for bone repair.
Gesehen am 04.07.2022